Feeding habits of culicine mosquitoes in the Cameroon lowland forests based on stable isotopes and blood meal analyses - Njabo, Kevin Yana; Smith, Thomas B.; Yohannes, Elizabeth (My University, 2013)
Mosquito blood feeding behavior is a very significant component of pathogen transmission and determinant of disease epidemiology. Yet, knowledge of foraging ecology of mosquitoes often depends on the presence of undigested blood in the mosquito mid gut. Approximately 36 h after feeding, the blood meal is sufficiently digested to make identification by molecular techniques difficult, leaving a very narrow window in which these methods can be utilized. Here, we investigated the feeding habits of wild caught culicine mosquitoes from four genera, Aedes, Anopheles, Coquillettidia and Mansonia of the lowland rainforests of Cameroon based on the isotopic ratios of nitrogen (δ15N), carbon (δ13C) and sulfur (δ34S). Results showed that unfed mosquitoes had a lower δ13C, δ15N and middle δ34S values than mosquitoes fed with δ13C appearing to be the best element to differentiate between mosquito species that fed on different host species. Isotopic analyses show that the different mosquito genera may be separated based on their diets, suggesting that linking stable isotope-based assays and DNA analysis may be a powerful new tool to investigate mosquito feeding ecology and the dynamics of vector-borne pathogens.
Keywords: Carbon (δ13C); nitrogen (δ15N); sulfur (δ34S); isotope; feeding habits; mosquitoes; polymerase chain reaction (PCR); 570